Anaerobic gut bacteria and their potential role in the initiation, exacerbation, and development of human colorectal cancer: a narrative review - Sahar Sabour; Sahar Sabour; Hanieh Sadeghi Koupaei; Hadi Ghasemi; Mansour Amin; Mansour Amin; Taher Azimi (Frontiers in Cellular and Infection Microbiology)
Colorectal cancer (CRC) is known as the second leading cause of cancer-related deaths around the world. Rectal bleeding, changes in bowel movements, weight loss, and fatigue are the main clinical presentations of CRC. While the exact etiology of the disease is unknown, CRC is considered a complex and multifactorial disease resulted from an intricate interplay of genetic and environmental factors. Moreover, CRC is known as a chronic inflammation–associated tumor, and patients with inflammatory bowel disease (IBD) or Irritable bowel syndrome (IBS) are susceptible groups to CRC development. The gut microbiota and its metabolites play a crucial role in the development and progression of CRC. CRC can be created after anaerobic bacterial infections such as Enterotoxigenic Bacteroides fragilis (ETBF), Fusobacterium, Clostridium difficile, Clostridium perfringens, Clostridium septicum, Peptostreptococcus, Prevotella, Veillonella, etc. Activation of Wnt signaling, loss of tissue architecture, proinflammatory signaling, and genotoxic cellular DNA damage are the primary mechanisms by which anaerobic bacteria induce carcinogenesis in CRC. Besides, spore germination and toxin production are done in hypoxic and acidic conditions. Therefore, according to the presence of this condition (anaerobic glycolysis) in tumor tissue, the tumor environment is suitable for the formation of anaerobic infections. The current review‐based study aims to discuss the important aspects of these mechanisms and their possible roles in the initiation, development, and exacerbation of CRC.